Уравнения:1) х²-3(х-2)+2х-12=02) 3х²-2(х²-2х)+2х-11=53) 5х²-3(х²+2х)+3х-13=44) х²-4|x|+2х-7=1Неравенство:1) 2х²+2≤3х+92) 3х²+5≤х+73) 2(х²+2)≤5х+11

Уравнения: 1) х²-3(х-2)+2х-12=0 2) 3х²-2(х²-2х)+2х-11=5 3) 5х²-3(х²+2х)+3х-13=4 4) х²-4|x|+2х-7=1 Неравенство: 1) 2х²+2≤3х+9 2) 3х²+5≤х+7 3) 2(х²+2)≤5х+11
Гость
Ответ(ы) на вопрос:
Гость
x^2-(3х-6)+2х-12=0 х^2-х-6=0 D=(-1)^2-4*1(-6)=25 х1= корень из 25-(-1)/2*1=5+(-1)/2=3 х2= корень из -25-(-1)/2*1=-5-(-1)/2=-2 /дробь
Не нашли ответ?
Ответить на вопрос
Похожие вопросы